Mapping and dynamics of the Bobo-Dioulasso dairy value chain (Burkina Faso) - Sib, Ollo; Gandema, Abdoul Kader; Koné, Amidou; Sodré, Etienne; Vall, Eric (2024)
This study is part of the Agroecology Initiative (AEI) and aims to produce a georeferenced database of upstream actors in the Bobo-Dioulasso basin milk chain. In the first part of the report, we present the methodological approach used in this study. This first part deals with the objectives assigned to the study after the scoping and meeting to clarify the expected results. The methodology used by the consultant team to collect the data and the difficulties encountered are also discussed. The second part of the report is devoted to presenting the results obtained.